ANALISIS SEMIOTIKA PUISI "SENDIRI" KARYA CHAIRIL ANWAR - Alfitria Nurinsyira Resta; R. Ika Mustika; Riana Dwi Lestari (Parole : Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2022)
This study aims to describe the meaning of the poem entitled "own" by Chairil Anwar, using a semiotic approach. This research was motivated by the curiosity and interest of researchers to analyze the signs contained in Chairil Anwar's poetry. Semiotics is the study of linguistics that studies signs in literary works. A sign in question is in the form of the theme of the poem, or the meaning of a word in a particular poem. The signs in the "own" poetry appear, then analyzed by using a semiotic approach, among which there are several aspects, namely symbols, icons, and indexes, which in the end give rise to a meaning. Semiotics and language are an inseparable series, especially in literary works. Semiotics plays a major role in a poem because it can provide an illustration and an understanding to the reader regarding the language conveyed in each stanza. The research method used in this study is a qualitative descriptive method by describing the results of poetry analysis based on the data obtained. The data in this study is a poem by the writer Chairil Anwar with his own title, this poem has a simple stanza, and contains a deep meaning.Â